(Remote) class is now in session: Consider antitrust issues in higher education. Issue 11 (19th January 2021) - Gutierrez, Iván Resendiz
Abstract : The Antitrust Division of the U.S. Department of Justice has recently indicated antitrust laws will be enforced vigorously and higher education institutions may be subject to that enforcement. Institutions would benefit from paying close attention to two areas in particular — financial aid policies and competitive information‐sharing.